2010
DOI: 10.4103/0970-1591.70591
|View full text |Cite
|
Sign up to set email alerts
|

Primary renal lymphoma mimicking renal cell carcinoma

Abstract: Primary renal lymphoma is very rare. Lymphomatous involvement of the kidney is often seen as a part of disseminated disease. The prognosis is usually poor with median survival less than a year. It is essential to differentiate between renal cell carcinoma and renal lymphoma in patients presenting with solitary renal masses. We present a 52-year-old lady who presented with a solitary renal mass and was diagnosed to have primary lymphoma of the kidney and discuss briefly about primary renal lymphoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…It has been suggested that the lymphoma may originate from the renal sinus lymphatics or lymph vessels located near the renal capsule and form cords that enter into renal parenchyma, or follow chronic inflammation (such as chronic pyelonephritis, Sjogren's Syndrome, Systemic Lupus Erythematosus, Epstein Barr Virus of mononucleosis). 6 Many of the documented cases of renal lymphoma are secondary, and postmortem studies have found that approximately 50% of patients who died of NHL had renal involvement. PRL most commonly affects older male subjects, those older than 60 years (mean age at diagnosis, 64 years), frequently unilateral, rarely bilateral.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been suggested that the lymphoma may originate from the renal sinus lymphatics or lymph vessels located near the renal capsule and form cords that enter into renal parenchyma, or follow chronic inflammation (such as chronic pyelonephritis, Sjogren's Syndrome, Systemic Lupus Erythematosus, Epstein Barr Virus of mononucleosis). 6 Many of the documented cases of renal lymphoma are secondary, and postmortem studies have found that approximately 50% of patients who died of NHL had renal involvement. PRL most commonly affects older male subjects, those older than 60 years (mean age at diagnosis, 64 years), frequently unilateral, rarely bilateral.…”
Section: Discussionmentioning
confidence: 99%
“…Survival is extremely low, approximately 75% of patients die within the first year after surgery. 6 The final prognosis can be improved by early diagnosis and systemic chemotherapy. There are several options for the diagnostic evaluation of a possible involvement of the kidney, including renal ultrasonography, intravenous urography, CT, magnetic resonance imaging, and nuclear medicine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This condition has been doubted along the years due to the fact that the kidney lacks lymphoid tissue; nevertheless, there has been certain case reports around the world with different clinical manifestations that support its existence [2]. It has been said that lymphomagenesis could originate from hematogenous route from subcapsular lymphatics, or by direct extension from retroperitoneal cavity, sometimes associated with chronic inflammatory diseases that could result in these types of lymphoma [3].…”
Section: Introductionmentioning
confidence: 99%